An epidemiological study of 97 cases of primary cicatricial alopecia in Iran - Akram Beheshtiroy; Fatemeh Hajmanoochehri; Fahim Hossienghamar (PAGEPress Publications, 2015)
Cicatricial alopecia can produce major psychosocial disturbance. This study aimed to evaluate epidemiological features of primary cicatricial alopecia (PCA). Epidemiological and histological types of scarring alopecia were determined. The chi-squared test and t-test were performed to examine the relationship between different variables using SPSS 16. A total of 97 cases, 35 (36.1%) men and 62 (63.9%) women, with an average age of 37 (SD=12.7), were included in this study. The female/male (F/M) ratio was 1.7:1 for total cases, 1.92:1 for the lymphocytic type, and 1:1.5 for the neutrophilic type. No relationship was found between type of job (indoor or outdoor), clinical findings and histological types. Discoid lupus erythematous (DLE) was the most common histological type (63.9%). PCA was found to mainly affect middle-aged individuals. The high percentage of DLE in the present study is in agreement with some similar studies.